Rational design of conjugated side chains for high-performance all-polymer solar cells. Issue 1 (3rd November 2017) - Huang, Wei; Li, Meilin; Lin, Fengyuan; Wu, Yang; Ke, Zhifan; Zhang, Xing; Ma, Rui; Yang, Tingbin; Ma, Wei; Liang, Yongye
Abstract : High-performance all-polymer solar cells were developed by employing an asymmetric benzo[1, 2- b :4, 5- b ′]dithiophene unit with one thiophene and one 4-methoxythiophene conjugated side chain in the donor polymer, which enabled fine-tuning of energy levels and phase separation. Abstract : With their rapid development in recent years, organic solar cells hold the exciting potential to be a groundbreaking form of solar harvesting technology. Among these, all-polymer solar cells (all-PSCs) stand out owing to various advantages such as complementary absorption and superior stability. However, the advance of all-PSCs has been greatly impeded by energy level mismatches and unfavorable morphology of the active layer. Here, we report a molecular engineering approach featuring asymmetrical 4-methoxythiophene/thiophene as conjugated side chains of the donor polymer to fine-tune the energy level alignment and phase separation. The corresponding polymer, namely, poly4-[5-(2-ethylhexyl)-4-methoxythiophen-2-yl]-8-[5-(2-ethylhexyl)thiophen-2-yl]benzo[1, 2- b :4, 5- b ′]dithiophene-alt-[bis(5-thiophene-2-yl)-5, 6-difluoro-2-(2-hexyldecyl)-2 H -benzo[ d ][1, 2, 3]triazole-4, 7-diyl] (PMOT32) exhibited a power conversion efficiency that exceeded 8.5% in all-PSCs with poly[ N, N ′-bis(2-octyldodecyl)-1, 4, 5, 8-naphthalenedicarboximide-2, 6-diyl]-alt-5, 5′-(2, 2′-bithiophene) (N2200) as the acceptor. PMOT32:N2200 also maintained good photovoltaic performance when processed as a thick film or from non-halogenated solvents. Detailed comparisons with two other polymers with pure thiophene or 4-methoxythiophene as their side chains revealed how these side chains affected the photovoltaic performance via energy level alignment and phase separation.